2002
DOI: 10.1038/sj.onc.1205871
|View full text |Cite
|
Sign up to set email alerts
|

Human p14Arf: an exquisite sensor of morphological changes and of short-lived perturbations in cell cycle and in nucleolar function

Abstract: The human Ink4a/Arf tumor suppressor locus encodes two distinct products: p16Ink4a which prevents phosphorylation and inactivation of the retinoblastoma protein and, p14Arf , a nucleolar protein which activates the function of the tumor suppressor p53 protein in the nucleoplasm in response to oncogenic stimulation through an as yet ill-defined mechanism. Here we show that the level of endogenous p14Arf and its balance between the nucleolus and the nucleoplasm in HeLa cells are exquisitely sensitive to changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…Overall, our findings are in complete accordance with an emerging concept that disruption of the nucleolus contributes to p53 signaling and growth suppression (11,56,66). The idea proposed by Rubbi and Milner is that high levels of DNA damage or other cellular stresses perturb the nucleolus, causing release of nucleolar proteins (such as ARF) into the nucleoplasm, which then bind Mdm2 and activate p53.…”
Section: Vol 25 2005 Npm Negatively Regulates Arf In Nucleoli 1267supporting
confidence: 78%
See 1 more Smart Citation
“…Overall, our findings are in complete accordance with an emerging concept that disruption of the nucleolus contributes to p53 signaling and growth suppression (11,56,66). The idea proposed by Rubbi and Milner is that high levels of DNA damage or other cellular stresses perturb the nucleolus, causing release of nucleolar proteins (such as ARF) into the nucleoplasm, which then bind Mdm2 and activate p53.…”
Section: Vol 25 2005 Npm Negatively Regulates Arf In Nucleoli 1267supporting
confidence: 78%
“…However, the fact that ARF resides in nucleoli in cells lacking Mdm2 argued that other mechanisms normally govern ARF localization. We suggest that NPM regulates that process, in agreement with the virtually superimposable subnuclear distributions of ARF and NPM throughout the cell cycle or in response to various drugs (11). Third, and most importantly, ARF's ability to activate p53 and inhibit growth was inversely related to cellular NPM levels and ARF's localization to nucleoli.…”
Section: Discussionsupporting
confidence: 54%
“…2A). Ki-67 is a proliferation marker whose presence in the nucleolus is cell cycle dependent (11). We found that Ki-67 was mainly nucleoplasmic in aspirin-treated cells and showed minimal colocalization with RelA ( Fig.…”
Section: Resultsmentioning
confidence: 79%
“…In SCC of the cervix (HeLa) cells, levels of endogenous p14 ARF and its distribution between the nucleolus and nucleoplasm are sensitive to changes in cell morphology, cell cycle, and nucleolar function (38). However, the role of p14 ARF localization in its function remains unclear, with studies showing that nucleolar localization is not sufficient for growth inhibition (17) and is dispensable for relocalization and stabilization of Hdm2/ Mdm2 and p53 (16,39).…”
Section: Discussionmentioning
confidence: 99%